A novel anti-slip control approach for railway vehicles with traction based on adhesion estimation with swarm intelligence - Zirek, Abdulkadir; Onat, Altan (SPRINGER, 2020)
Anti-slip control systems are essential for railway vehicle systems with traction. In order to propose an effective anti-slip control system, adhesion information between wheel and rail can be useful. However, direct measurement or observation of adhesion condition for a railway vehicle in operation is quite demanding. Therefore, a proportional-integral controller, which operates simultaneously with a recently proposed swarm intelligence-based adhesion estimation algorithm, is proposed in this study. This approach provides determination of the adhesion optimum on the adhesion-slip curve so that a reference slip value for the controller can be determined according to the adhesion conditions between wheel and rail. To validate the methodology, a tram wheel test stand with an independently rotating wheel, which is a model of some low floor trams produced in Czechia, is considered. Results reveal that this new approach is more effective than a conventional controller without adhesion condition estimation.
Nový přístup k regulaci protiskluzové ochrany kolejových vozidel založený na stanovení adhezních podmínek s využitím principů swarm intelligence
Keywords: adhesion estimation; traction control; anti-slip control; railway vehicles; roller-rigs; swarm intelligence; odhad adhezních podmínek; řízení trakce; protiskluzová ochrana; kolejová vozidla; kladkové zkušební stavy; swarm intelligence